Analisis Unsur Matematika pada Motif Sulam Usus - Leni Zuni Isnawati; Fredi Ganda Putra (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2017)
The purpose of this article is to determine whether there are elements of mathematics contained in the intestine motif based on the concept of geometry. Subjects in this study consisted of 4 people obtained by purposive sampling technique. From the results of data analysis conducted by using descriptive analysis and discussion as follows 1) Intestinal embroidery motif contains the meaning of mathematics and culture or often called ethnomathematics. On the meaning of culture there is a link between the embroidery intestines with a culture that has been there before as the existence of cultural linkage between Hindu belief Buddhism and there are similarities of motifs and decorative patterns contained in the motif embroidery intestine with ornamental variety in Indonesia; 2) The relationship between the intestines with mathematical motifs there are elements of mathematics such as geometry elements in the form of geometry of dimension one and dimension two, and the geometry of transformation. The concept of one dimensional geometry is a line, while the two dimensions are elliptical and rhombic. The concept of transformation geometry includes reflection or reflection, in which case this reflection is most prevalent in a motif contained in the intestinal embroidery motif, dilation or diminution and enlargement, rotation or rotation and translation is a shift.